The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.4141/cjss2013-087
|View full text |Cite
|
Sign up to set email alerts
|

Soil properties following long-term application of stockpiled feedlot manure containing straw or wood-chip bedding under barley silage production

Abstract: Miller, J. J., Beasley, B. W., Drury, C. F., Hao, X. and Larney, F. J. 2014. Soil properties following long-term application of stockpiled feedlot manure containing straw or wood-chip bedding under barley silage production. Can. J. Soil Sci. 94: 389–402. The influence of long-term land application of stockpiled feedlot manure (SM) containing either wood-chip (SM-WD) or straw (SM-ST) bedding on soil properties during the barley (Hordeum vulgare L.) silage growing season is unknown. The main objective of our stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 40 publications
0
10
1
Order By: Relevance
“…2). Similarly, a positive linear relationship between soil respiration and SOC was reported by Kaiser et al (1992), Haney et al (2012), andMiller et al (2014), with R 2 values ranging from 0.35 to 0.70. Haney et al (2012) reported a stronger relationship (R 2 = 0.84) between soil respiration and water-extractable SOC than SOC.…”
Section: Soil Organic Matter and Solvita Carbon Dioxide Respirationmentioning
confidence: 59%
See 1 more Smart Citation
“…2). Similarly, a positive linear relationship between soil respiration and SOC was reported by Kaiser et al (1992), Haney et al (2012), andMiller et al (2014), with R 2 values ranging from 0.35 to 0.70. Haney et al (2012) reported a stronger relationship (R 2 = 0.84) between soil respiration and water-extractable SOC than SOC.…”
Section: Soil Organic Matter and Solvita Carbon Dioxide Respirationmentioning
confidence: 59%
“…Soil respiration is a reliable and useful indicator of easily decomposable organic C and an important indicator of soil quality and fertility (Haney et al, 2008;Monaco et al, 2008;Iovieno et al, 2009), and there is generally a positive linear relationship between soil respiration and SOC, with R 2 values ranging from 0.35 to 0.70 (Kaiser et al, 1992;Haney et al, 2012;Miller et al, 2014). Iovieno et al (2009) reported an increase in SOC with compost application after 3 yr and found that compost application increased soil respiration from 0.68 mg CO 2 g −1 dry weight h −1 (no compost applied) to 1.18 mg CO 2 g −1 dry weight h −1 when compost was applied at 45 Mg ha −1 yr −1 , reflecting the higher available C pool.…”
mentioning
confidence: 99%
“…Annual beef manure application rates in this area range from approximately 13 to 57 Mg ha ¡1 (dry wt. ), with a mean value of 38 Mg ha ¡1 (Miller et al 2014). Our application rates were slightly lower than the rates (35-104 Mg ha ¡1 dry wt., 60-180 Mg ha ¡1 wet wt.)…”
Section: Methodsmentioning
confidence: 99%
“…However, it is unlikely that the greater soil Nm for ST than WD was caused by differences in total N of amendments as mean total N was very similar for stockpiled manure with ST (16.4 g kg −1 ) and WD (15.8 g kg −1 ) treatments (Miller et al 2009). The greater Nm rates for ST than WD were likely not caused by a greater supply of organic N. The total N concentration of the surface (0-15 cm) soil in 2011 and 2012 after 13-14 annual applications was similar for ST and WD with stockpiled manure (Miller et al 2014).…”
Section: Discussionmentioning
confidence: 80%
“…caused by a greater quantity of N in the more readily available (<14 d) and intermediate (14-308 d) mineralizable N pools, as well as the greater rate of N turnover (k value or rate coefficient) that was found for ST than WD after 8 yr (Sharifi et al 2014). In addition, significantly greater water-soluble total N and lower C:N ratios in ST-than WD-amended soils after 13-14 yr (Miller et al 2014) may have also contributed to greater Nm. Previous research has shown that Nm rates may be increased by greater water-soluble total N (Qafoku et al 2001;Morvan and Nicolardot 2009;Khalili and Nourbakhsh 2012) and lower C:N ratios (Eghball et al 2002;Qian and Schoenau 2002;Cabrera et al 2005).…”
Section: Discussionmentioning
confidence: 97%